Dissociating eye-movements and comprehension during film viewing - Hutson, John (Kansas State University, 2016)
Film is a ubiquitous medium. However, the process by which we comprehend film narratives is not well understood. Reading research has shown a strong connection between eye-movements and comprehension. In four experiments we tested whether the eye-movement and comprehension relationship held for films. This was done by manipulating viewer comprehension by starting participants at different points in a film, and then tracking their eyes. Overall, the manipulation created large differences in comprehension, but only found small difference in eye-movements. In a condition of the final experiment, a task manipulation was designed to prioritize different stimulus features. This task manipulation created large differences in eye-movements when compared to participants freely viewing the clip. These results indicate that with the implicit task of narrative comprehension, top-down comprehension processes have little effect on eye-movements. To allow for strong, volitional top-down control of eye-movements in film, task manipulations need to make features that are important to comprehension irrelevant to the task.
Keywords: Visual Cognition; Eye-Movements; Event Cognition; Narrative Comprehension